Analisis Pembelajaran Steam Di Sekolah Dasar Berbasis Kurikulum Merdeka: Analysis of STEAM Based Learning in Elementary Schools within the Framework of the Merdeka Curriculum - Faridah, Siti; Saputra, Ridho Indra; Ramadhani, Muhammad Ihsan (Anterior Jurnal, 2025)
This study aims to analyze the implementation of Science, Technology, Engineering, Arts, and Mathematics (STEAM) learning in elementary schools within the framework of the Merdeka Curriculum. A qualitative method was employed through observations, interviews, and lesson plan analysis. The findings reveal that STEAM learning has begun to be integrated by connecting various disciplines under the theme of environmental care, such as recycling activities, creating cleanliness posters, and calculating waste volume. This approach encouraged students to become more enthusiastic, creative, confident, and collaborative in group activities. However, the successful implementation of STEAM in elementary schools still requires stronger support from schools and educational policies, particularly in providing adequate facilities and enhancing teachers’ competencies. Overall, STEAM learning shows great potential to support the Merdeka Curriculum while fostering 21st-century skills among students, including critical thinking, creativity, collaboration, and communication